Quantitation of the antibody response in african swine fever virus infection. I: Adaptation of an enzimeimmunoaáay using monoclonal antibodies against different isotypes of immunoglobulins - Hortiguela, O.=700 1 Sanchez-Vizcaino, J.M.; Arias, M.
(Es, En)
ilus., 15 ref.
Keywords: PESTE PORCINA AFRICANA; ANTICUERPOS; ESPAÑA; CUANTIFICACION; ELISA